Commandeering Channel Voltage Sensors for Secretion, Cell Turgor, and Volume Control. (January 2017) - Karnik, Rucha; Waghmare, Sakharam; Zhang, Ben; Larson, Emily; Lefoulon, Cécile; Gonzalez, Wendy; Blatt, Michael R.
Abstract : Control of cell volume and osmolarity is central to cellular homeostasis in all eukaryotes. It lies at the heart of the century-old problem of how plants regulate turgor, mineral and water transport. Plants use strongly electrogenic H + -ATPases, and the substantial membrane voltages they foster, to drive solute accumulation and generate turgor pressure for cell expansion. Vesicle traffic adds membrane surface and contributes to wall remodelling as the cell grows. Although a balance between vesicle traffic and ion transport is essential for cell turgor and volume control, the mechanisms coordinating these processes have remained obscure. Recent discoveries have now uncovered interactions between conserved subsets of soluble N -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins that drive the final steps in secretory vesicle traffic and ion channels that mediate in inorganic solute uptake. These findings establish the core of molecular links, previously unanticipated, that coordinate cellular homeostasis and cell expansion. Trends: Vesicle trafficking (SNARE) proteins 'commandeer' the voltage sensor domains of Kv channels to confer a voltage dependence on secretory traffic for coordination with ion transport during cell expansion. Sec1/Munc18 (SM) protein-mediated regulation of secretion is selective among plasma membrane SNAREs. SM proteins and Kv channels bind the SNARE SYP121 at overlapping sites, implying a sequential interplay between these proteins to coordinate membrane traffic and transport.